Comparison of the diagnostic accuracy of CBCT and conventional CT in detecting degenerative osseous changes of the TMJ: A systematic review - Ranjeni Rajamani Veerappan; Maragathavalli Gopal (Wolters Kluwer Medknow Publications, 2015)
Temporomandibular joint (TMJ) disorders are a group of conditions that cause pain and dysfunction in the jaw joint and muscles that control jaw movement. According to the Research Diagnostic Criteria (RDC/TMD), temporomandibular disorders (TMDs) may be classified into three different groups: a) myofacial pain dysfunction syndrome (MPDS), b) internal derangement, and c) arthritis. Complicated anatomy of the TMJ was the reason for developing standardized radiographic techniques to diagnose TMDs. The introduction of computed tomography (CT) in the diagnosis of TMJ disorders enabled much better delineation of anatomical structures of the joint due to lack of tissue superposition. Cone beam CT (CBCT) is the latest imaging modality for craniofacial deformities, with a lesser radiation exposure and cheaper cost when compared to CT. A systematic literature search was done to identify articles describing degenerative osseous changes of the TMJ using CBCT and conventional CT. Electronic search of scientific papers was carried out in PubMed (MeSH), ScienceDirect, and Cochrane databases using specific keywords. In this systematic review, all the selected articles demonstrate the role of CBCT and CT in diagnosing the degenerative osseous changes of the TMJ. The studies included in the review suggested that CT has been the method of choice to assess the TMJ dynamics and contours of the cortical bone.